Identifying personal beliefs of nursing staff about encouraging psychogeriatric nursing home residents in daily activities: A qualitative study. Issue 4 (17th November 2022) - van Sambeek, Joyce; Metzelthin, Silke; Zwakhalen, Sandra; Vluggen, Stan
Abstract: Aim: To identify personal beliefs of Dutch nursing staff about encouraging psychogeriatric nursing home residents in daily activities. Design: Qualitative study following COREQ guidelines. Methods: Fifteen semi‐structured interviews with Dutch nursing staff of wards hosting psychogeriatric residents were conducted in Spring 2021. Data were systematically analysed through deductive coding analysis in NVivo. Results: Most nurses indicated to encourage residents frequently to perform activities independently, although many also indicated to take over tasks habitually. Nurses seemed to show sufficient awareness, reflected by adequate knowledge of what encouraging residents entailed and insight in the risks of not encouraging residents. Nurses' motivation to encourage residents seemed high, reflected by expressing multiple advantageous and few disadvantageous beliefs and a high willingness to encourage residents. Managerial support was perceived ambiguous. Self‐efficacy was perceived high, although little time, staffing shortages and resistance of residents reduced self‐efficacy. Nurses were often unable to anticipate such situations and expressed the need of skills, e.g. patience.